Effects of Pirfenidone and Collagen-Polyvinylpyrrolidone on Macroscopic and Microscopic Changes, TGF-β1 Expression, and Collagen Deposition in an Experimental Model of Tracheal Wound Healing. (11th May 2017) - Olmos-Zuñiga, J. Raúl; Silva-Martínez, Mariana; Jasso-Victoria, Rogelio; Baltazares-Lipp, Matilde; Hernández-Jiménez, Claudia; Buendía-Roldan, Ivette; Jasso-Arenas, Jazmin; Martínez-Salas, Alan; Calyeca-Gómez, Jazmin; Guzmán-Cedillo, Axel E.; Gaxiola-Gaxiola, Miguel; Romero-Romero, Laura
Abstract : Tracheal stenosis (TS) is a fibrosis originated by prolonged inflammation and increased transforming growth factor beta 1 (TGF- β 1) expression and collagen deposition (CD) in the tracheal wound. Several wound-healing modulators (WHMs) have been used to modulate the tracheal healing process and prevent TS, but they have failed, justifying the need to evaluate alternative WHM. The pirfenidone (PFD) and collagen-polyvinylpyrrolidone (Collagen-PVP) decrease inflammation and fibrosis. This study assessed the effect of PFD administration and Collagen-PVP topical application on macroscopic and microscopic changes, TGF- β 1 expression, and CD in an experimental model of tracheal wound healing. Forty Wistar rats underwent cervical tracheoplasty, were divided into 4 groups (n = 10 ), and were treated with different WHM: group I, saline solution (SS); group II, Collagen-PVP; group III, mitomycin C (MMC); and group IV, 40 mg/kg PFD. Four weeks after surgery, the macroscopic and microscopic changes, in situ TGF- β 1 expression, and CD in posttracheoplasty scars were evaluated. The animals treated with Collagen-PVP and PFD developed less inflammation and fibrosis than animals in the other study groups (p < 0.05, Kruskal-Wallis) and, moreover, showed lower TGF- β 1 expression and CD than animals in group I (p < 0.05, ANOVA and Tukey's test). In conclusion, PFD and Collagen-PVP decrease inflammation, fibrosis, TGF β -1 expression, and CD in the posttracheoplasty rats' scar.